UPAYA MENINGKATKAN DISIPLIN SISWA PADA TATA TERTIB SEKOLAH DENGAN MENGGUNAKN TEKNIK POSITIVE REINFORCEMENT PADA SISWA KELAS IX SMP SATYA DHARMA SUDJANA GUNUNG MADU TAHUN AJARAN 2012/2013 - Cempaka Puri; Yusmansyah Yusmansyah; Ratna Widiastuti (ALIBKIN (Jurnal Bimbingan Konseling), 2013)
The problem this research was whether of positive reinforcement could increase students’ dicipline toward the school rule at the nineth grade of SMP Satya Dharma Sudjana Gunung Madu academic year 2012/2013. The objective of this research was to find out the use of positive reinforcement in increasing students’ dicipline toward the school rule at the nineth grade of SMP Satya Dharma Sudjana Gunung Madu academic year 2012/2013. The researcher used kuasi experiment with one group pretest-posttest experiment design. There were six students had poor dicipline toward school rule. The data collection of the research was through partipants observation and interview. The result showed that positive reinforcement technique could increase students’ dicipline toward the school rule at the nineth grade. It was showed from the result of data analysis, using wilcoxon test. The result of pretest and posttest was p= 0.026; p 0.05. So, H0 was rejected and Ha was accepted. It could be inferred that positive reinforcement could increase students’ dicipline at the nineth grade of SMP. The conclusion of this research was positive reinforcement could increase students’ dicipline at the nineth grade of SMP Satya Dharma Sudjana Gunung Madu academic year 2012/2013. The suggestions that given were: (1) The students have to try to increase their dicipline, so in doing their activity students do not face the obstacle in daily life with their friends, teachers, and others. Especially for students as the subject of this research, the students should increase their dicipline toward the school rule. (2)for teachers, the teachers are expected to give information to the students about the important of dicipline to in increase the students’ dicipline actively. (3) the researcher hope to the others to do the same research but use the old different subject.Key word: students’ dicipline, positive reinforcement tehnique.